Electrical and Mechanical Properties of Post-annealed SiC(x)N(y) Films - Fraga, M. A.; Massi, M.; Oliveira, I. C.; Cruz, Nilson Cristino da [UNESP]; Santos Filho, S. G. dos (Trans Tech Publications Ltd, 2009)
Amorphous SiC(x)N(y) films have been deposited on (100) Si substrates by RF magnetron sputtering of a SiC target in a variable nitrogen-argon atmosphere. The as-deposited films were submitted to thermal anneling in a furnace under argon atmosphere at 1000 degrees C for 1 hour. Composition and structure of unannealed and annealed samples were investigated by RBS and FTIR. To study the electrical characteristics of SiC(x)N(y) films, Metal-insulator-semiconductor (MIS) structures were fabricated. Elastic modulus and hardness of the films were determined by nanoindentation. The results of these studies showed that nitrogen content and thermal annealing affect the electrical, mechanical and structural properties of SiC(x)N(y) films.
Keywords: Silicon carbon nitride; Thermal annealing; Resistivity; Elastic modulus; Hardness